Mineralogy and petrogenesis of pegmatites in the Spruce Pine District, North Carolina, USA - Swanson,S.E.; Veal,W.B. (Journal of Geosciences, 2010)
Granitic rocks (mainly granodiorites) of the Spruce Pine Plutonic Suite occur as small plutons and numerous pegmatite bodies intruded into amphibolite-grade schists and gneisses of the Ashe Formation. Intrusion ages range from 377 to 404 Ma and are near the peak of amphibolite-facies metamorphism in the country rocks. The granodiorites have a mortar texture with coarse (˜ 1 cm) grains of feldspar, quartz and muscovite enclosed in a finer grained matrix of the same phases. Large (10-30 cm) crystals of perthitic K-feldspar and plagioclase occur in the granodiorite. Pegmatites occur within the granodiorite and as isolated intrusions within the country rocks. Contacts between pegmatites and host granodiorites range from sharp, cross-cutting to completely gradational. Some of the plutons contain up to 50 % pegmatite. Pegmatite mineralogy is similar to the granodiorites; major amounts of feldspars and quartz, accessory amounts of muscovite, garnet, and epidote. Secondary minerals, formed by subsolidus recrystallization, include epidote, muscovite, quartz, and grossular garnet. A few of the pegmatites are more fractionated and contain tourmaline and beryl. Compositions of feldspars, muscovite, and garnet show some regional variation, but are generally similar for pegmatites and associated granodiorite. About half of the pegmatites are unzoned. Zoning in the pegmatites is simple with a quartz core, an intermediate zone of graphic granite, plagioclase and muscovite and an outer finer grained zone that locally shows mineral layering parallel to the contact. The abundance of pegmatitic textures relative to granitoid textures in the Spruce Pine Plutonic Suite is related to the depth of crystallization. Spruce Pine granitoids crystallized at depths of 20-30 km (0.7 to 1.1 GPa) based on feldspar thermobarometry and experimentally determined melting relations. Skeletal crystals of quartz and feldspar along with plumose muscovite clusters are common in the Spruce Pine pegmatites. Water content of magmas at such high pressures can be high. The subtle transition from granitic to pegmatitic texture so common at Spruce Pine (and in other deep-seated systems) was probably related to the development of zones of water-enriched magma and delayed nucleation in the hydrous melts. Deformation (evidenced by mortar texture) of the Spruce Pine Plutonic Suite was related to later regional deformation.
Keywords: Spruce Pine; pegmatites; mineralogy; North Carolina